Frustration across the periodic table: heterolytic cleavage of dihydrogen by metal complexes. (24th July 2017) - Bullock, R. Morris; Chambers, Geoffrey M.
Abstract : This perspective examines frustrated Lewis pairs (FLPs) in the context of heterolytic cleavage of H2 by transition metal complexes, with an emphasis on molecular complexes bearing an intramolecular Lewis base. FLPs have traditionally been associated with main group compounds, yet many reactions of transition metal complexes support a broader classification of FLPs that includes certain types of transition metal complexes with reactivity resembling main group-based FLPs. This article surveys transition metal complexes that heterolytically cleave H2, which vary in the degree that the Lewis pairs within these systems interact. Many of the examples include complexes bearing a pendant amine functioning as the base with the metal functioning as the hydride acceptor. Consideration of transition metal compounds in the context of FLPs can inspire new innovations and improvements in transition metal catalysis. This article is part of the themed issue 'Frustrated Lewis pair chemistry'.